Case Studies in Food Freezing at Very Low Temperature. (November 2016) - Biglia, Alessandro; Comba, Lorenzo; Fabrizio, Enrico; Gay, Paolo; Aimonino, Davide Ricauda
Abstract: Freezing is one of the most widely used and effective processes to preserve foods shelf-life during long periods of time. This paper focuses on very low temperature freezing, and a thermal model, based on literature formulations, was developed to calculate the food freezing time considering several kinds of food, with different sizes, shapes and chemical composition. Moreover, once evaluated the food freezing time as a function of temperature and velocity of the cooling fluid, a chart reporting the food production rate, the freezing time and the cooling capacity was developed to properly design the freezing equipment in terms of optimal choice of the process and type of freezer.